Assessing the Effect of Façade Materials, Urban canyon, and Orientation on Outdoor Thermal Comfort in a Mediterranean City: A Case Study of Hebron, Palestine - Nader Zatary , Raghad (Palestine Polytechnic University, 2026)
Abstract Outdoor thermal comfort is one of the most significant challenges in cities within a Mediterranean climate, as it significantly impacts the health and well-being of residents and the quality of the urban environment, many variables influence outdoor thermal comfort. In this context, the study aims to investigate the combined effect of facade materials, street orientation, and urban canyon on outdoor thermal comfort indicators in the commercial center of Hebron. A mixed-method approach was adopted, combining field measurements of air temperature, relative humidity, and wind speed with ENVI-met V5.6.1 simulations, following calibration and validation procedures. Three streets with different orientations and canyon configurations were analyzed, and nine façade material scenarios were evaluated based on their thermo- physical properties. Thermal performance was evaluated using comfort indices (PET and UTCI) in summer and winter, using statistical methods to test the significance of differences between certain scenarios and identify the most influential factors. The results indicate that facade materials and urban canyon configurations together significantly affect thermal comfort levels. According to the statistical analysis, material alone affects outdoor thermal comfort. The best street orientations are north-south and northwest- southeast, while the worst orientation is east-west. The best value for urban canyons ranges from 1 to 2. The study highlights the importance of integrating material properties with urban configuration to improve outdoor thermal conditions in Mediterranean commercial streets and provides evidence-based insights to support climate-responsive urban design. Keywords: outdoor thermal comfort/performance, urban canyon, building façade, orientation, statistical analysis, Envi met تش ّكل الراحة الحرارية الخارجية أحد أبرز التحديات في المدن ذات المناخ المتوسطي، لما لها من تأثير كبير على صحة ورفاهية السكان وجودة البيئة الحضرية. هناك العديد من المتغيرات التي تؤثر على الراحة الحرارية الخارجية ،وفي هذا السياق، تهدف هذه الدراسة إلى تحليل الأثر المشترك لمواد الواجهات، وتو ّجه الشوارع، والوادي الحضري على مؤشرات الراحة الحرارية الخارجية في المركز التجاري لمدينة الخليل. اعتمدت الدراسة على منهجية مزدوجة جمعت بين القياسات الميدانية لدرجة الحرارة، والرطوبة النسبية، وسرعة الرياح والمحاكاة باستخدام برنامج 5.6.1V met-ENVI بعد إجراء معايرة وتحقق لضمان دقته. وتم تحليل ثلاثة شوارع ذات اتجاهات وتكوينات مختلفة للمباني،كما تم تقييم تسعة سيناريوهات لمواد الواجهات بنا ًء على خصائصها الحرارية والفيزيائية. ّم الأداء الحراري باستخدام مؤشرات الراحة الحرارية ( وقُ PET وUTCI (في الصيف والشتاء، باستخدام أساليب إحصائية يِ لاختبار دلالة الفروق بين سيناريوهات محددة وتحديد العوامل الأكثر تأثي ًرا. أظهرت النتائج أن مواد الواجهات وتكوين الوادي الحضري تؤثر بشكل كبير على مستويات الراحة الحرارية. ا للتحليل ووفقً الإحصائي، تؤثر المادة وحدها على الراحة الحرارية الخارجية. أفضل اتجاهات الشوارع هي الشمال-الجنوب والشمال الغربي-الجنوب الشرقي، بينما أسوأها هو الشرق-الغرب. تتراوح أفضل قيمة للشوارع الحضرية بين ١ و.٢ تُبرز هذه الدراسة أهمية دمج خصائص المواد مع التصميم الحضري لتحسين الظروف الحرارية الخارجية في الشوارع التجارية المتوسطية، وتقدم رؤى قائمة على الأدلة لدعم التصميم الحضري ال ُمراعي للمناخ.
Number of pages236
Keywords: outdoor thermal comfort/performance; urban canyon; building façade; orientation; statistical analysis; Envi met